The Impact of the Implementation of the Rural Empowerment and Agricultural Development Scaling Up Initiative (READSI) Program on Community Empowerment - Asniar, Asniar; Boceng, Annas; Suryanto, Suryanto (Riwayat: Educational Journal of History and Humanities, 2025)
Objective: to analyze the role of agricultural extension workers in the implementation of the Rural Empowerment and Agricultural Development Scaling Up Initiative (READSI) program on empowering cocoa farmers in Lasusua district, North Kolaka regency and to analyze the impact of the Rural Empowerment and Agricultural Development Scaling Up Initiative (READSI) program on farmer empowerment in terms of cocoa farming income through field school activities (SL-Kakao) in Lasusua district, North Kolaka regency. Method: this type of research is descriptive research with a quantitative approach. This research is more specific using a case study method. Results: the role of extension workers of the READSI program in Lasusua district is quite effective. As a dynamic, their role is classified as moderate because there are still challenges in increasing the independence and networking of farmer groups. However, their role as facilitators and motivators is classified as high, as seen from the success in delivering technology and increasing farmer enthusiasm. As a liaison, extension workers are very successful in bridging farmers with various parties, strengthening agribusiness networks, and facilitating access to resources. Conclusion: Overall, the synergistic role of extension workers has supported the increase in capacity and independence of cocoa farmers, while accelerating the successful implementation of the READSI program in Lasusua district, North Kolaka regency.